2020
DOI: 10.1016/j.ajhg.2020.06.014
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in MYLPF Cause a Novel Segmental Amyoplasia that Manifests as Distal Arthrogryposis

Abstract: We identified ten persons in six consanguineous families with distal arthrogryposis (DA) who had congenital contractures, scoliosis, and short stature. Exome sequencing revealed that each affected person was homozygous for one of two different rare variants (c.470G>T [p.Cys157Phe] or c.469T>C [p.Cys157Arg]) affecting the same residue of myosin light chain, phosphorylatable, fast skeletal muscle (MYLPF). In a seventh family, a c.487G>A (p.Gly163Ser) variant in MYLPF arose de novo in a father, who transmitted it… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 57 publications
(61 reference statements)
1
23
0
Order By: Relevance
“…The TPM2 muscle morphogenesis defects we have observed in Drosophila, zebrafish, and cultured cells are likely the result of improperly regulated actin dynamics in migrating myoblasts or in elongating myotubes that expressed pathogenic variants. DA and amyoplasia (absence of muscle) were often thought to be distinct clinical diagnoses, but amyoplasia was recently reported in a case of congenital DA (Chong et al, 2020). Our studies provide additional support for a model in which DA variants disrupt muscle development.…”
Section: Discussionsupporting
confidence: 66%
“…The TPM2 muscle morphogenesis defects we have observed in Drosophila, zebrafish, and cultured cells are likely the result of improperly regulated actin dynamics in migrating myoblasts or in elongating myotubes that expressed pathogenic variants. DA and amyoplasia (absence of muscle) were often thought to be distinct clinical diagnoses, but amyoplasia was recently reported in a case of congenital DA (Chong et al, 2020). Our studies provide additional support for a model in which DA variants disrupt muscle development.…”
Section: Discussionsupporting
confidence: 66%
“…Exome sequencing recently identified MYLPF, a phosphorylatable fast skeletal muscle regulatory light chain, as a cause of DA [23]. Some affected individuals were homozygous for rare variants in the gene, while other individuals have autosomal dominant disease, a finding similar to what was described for MYH3-related disorders.…”
Section: Mylpfmentioning
confidence: 59%
“…However, unlike MYH3-related disorders, the phenotypes for MYLPF autosomal dominant and recessive conditions are apparently indistinguishable. Protein modeling of MYLPF alleles suggested that the autosomal dominant pathogenic variants cause disease through their direct interaction with myosin, while the recessive alleles only indirectly affect the interaction with myosin [23].…”
Section: Mylpfmentioning
confidence: 99%
See 1 more Smart Citation
“…Genomes were sequenced to >95% at >10× coverage and >90% at 20× coverage. In brief, data were annotated using Variant Effect Predictor v95.3 (McLaren et al, 2016) and analyzed using GEMINI v0.30.1 (Paila et al, 2013) as previously described (Chong et al, 2020). All variants were filtered to remove low‐quality sites, requiring a minimum read depth of 6, a minimum genotyping quality of 20, and the absence of any Genome Analysis Tookit filter flags.…”
Section: Methodsmentioning
confidence: 99%